Yedoma Cryostratigraphy of Recently Excavated Sections of the CRREL Permafrost Tunnel Near Fairbanks, Alaska - Kanevskiy, Mikhail; Shur, Yuri; Bigelow, Nancy H.; Bjella, Kevin L.; Douglas, Thomas A.; Fortier, Daniel; Jones, Benjamin M.; Jorgenson, M. Torre (Frontiers in Earth Science, 2022)
Recent excavation in the new CRREL Permafrost Tunnel in Fox, Alaska provides a unique opportunity to study properties of Yedoma — late Pleistocene ice- and organic-rich syngenetic permafrost. Yedoma has been described at numerous sites across Interior Alaska, mainly within the Yukon-Tanana upland. The most comprehensive data on the structure and properties of Yedoma in this area have been obtained in the CRREL Permafrost Tunnel near Fairbanks — one of the most accessible large-scale exposures of Yedoma permafrost on Earth, which became available to researchers in the mid-1960s. Expansion of the new ∼4-m-high and ∼4-m-wide linear excavations, started in 2011 and ongoing, exposes an additional 300 m of well-preserved Yedoma and provides access to sediments deposited over the past 40,000 years, which will allow us to quantify rates and patterns of formation of syngenetic permafrost, depositional history and biogeochemical characteristics of Yedoma, and its response to a warmer climate. In this paper, we present results of detailed cryostratigraphic studies in the Tunnel and adjacent area. Data from our study include ground-ice content, the stable water isotope composition of the variety of ground-ice bodies, and radiocarbon age dates. Based on cryostratigraphic mapping of the Tunnel and results of drilling above and inside the Tunnel, six main cryostratigraphic units have been distinguished: 1) active layer; 2) modern intermediate layer (ice-rich silt); 3) relatively ice-poor Yedoma silt reworked by thermal erosion and thermokarst during the Holocene; 4) ice-rich late Pleistocene Yedoma silt with large ice wedges; 5) relatively ice-poor fluvial gravel; and 6) ice-poor bedrock. Our studies reveal significant differences in cryostratigraphy of the new and old CRREL Permafrost Tunnel facilities. Original syngenetic permafrost in the new Tunnel has been better preserved and less affected by erosional events during the period of Yedoma formation, although numerous features (e.g., bodies of thermokarst-cave ice, thaw unconformities, buried gullies) indicate the original Yedoma silt in the recently excavated sections was also reworked to some extent by thermokarst and thermal erosion during the late Pleistocene and Holocene.